Acute cholangitis: a literature review - Orozco, Cesár A. O.; Fuentes, Alberto B.; Gutiérrez, Félix O.; Z. Torres, Jose M. (International Surgery Journal, 2022)
Acute cholangitis is a disease that occurs when a stricture or obstruction of the bile duct causes cholestasis and/or infection. Biliary stricture or obstruction elevates the pressure in the biliary system and causes reflux of microorganisms or endotoxins from the infected bile into the systemic circulation, which induces a systemic inflammatory response. The Charcot triad provides high specificity, however, due to its low sensitivity (50-70%), it is very limited to make a diagnosis of cholangitis alone. Therefore, the most current guidelines suggest specific criteria for diagnosis. Antibiotic treatment is a fundamental pillar in the management of patients with cholangitis. The treatment must be carried out depending on the severity (grade I-III).